Reflections on state obligations with respect to economic, social and cultural rights in international human rights law - Ssenyonjo, Manisuli (The International Journal of Human Rights, 2011)
In 1948 the Universal Declaration of Human Rights (UDHR) declared a wide range of human rights including economic, social and cultural rights as a ‘common standard of achievement’ for all peoples and all nations. At an international level, these rights were reinforced by a legally binding international treaty, the International Covenant on Economic, Social and Cultural Rights (ICESCR) in 1966, and more recently by the Optional Protocol to the ICESCR as adopted by the UN General Assembly on 10 December 2008, and opened for signature on 24 September 2009. Despite these positive developments, six decades after the UDHR, there are still questions regarding the status of economic, social and cultural rights as human rights in international law. In particular, four key questions regarding these rights, are addressed in this article: (1) what are the real human rights obligations of states parties to the ICESCR? (2) Are such obligations territorially limited or is there scope for extra-territorial obligations? (3) Are states permitted to derogate from (some) economic, social and cultural (ESC) rights during emergencies despite the fact that the ICESCR does not contain a derogation clause either permitting or prohibiting derogations? (4) Was it really necessary to adopt in 2008 an Optional Protocol to the ICESCR to provide for the competence of the committee monitoring the obligations of states parties under the ICESCR, the Committee on Economic, Social and Cultural Rights, to receive and consider communications alleging violations of any of the rights protected by the ICESCR? And should states parties to the ICESCR sign and ratify this Optional Protocol without delay?
Keywords: economic; social and cultural rights; state obligations; International Covenant on Economic; Social and Cultural Rights; extra-territorial human rights obligations; non-derogable rights; Optional Protocol to the International Covenant on Economic; Social and Cultural Rights